Surprise and Suspense: How the Intelligence Community Forgot the Future. Issue 3 (2nd September 2021) - Alessa, Lilian; Moon, Sean K; Valentine, James; Marks, Michael; Hepburn, Don; Kliskey, Andrew
ABSTRACT: This paper examines the challenges faced by the U.S. intelligence community (IC) in recognizing and responding to the elements inherent in asymmetric competition with China. We offer that cultural and procedural impediments are negatively impacting the community's capabilities and argue that reliance on outdated methodologies and ad hoc technology acquisition to detect activities specific to asymmetric competition has allowed adversaries to exploit three types of interstitial gray areas (IGA) – operational, organizational, and informational. We argue that an updated framework to combat emerging threats from asymmetric competition and commensurate IGAs that has been proven in field settings to enhance detection, deterrence, denial, diplomacy, and defense against adversarial actions is needed. We demonstrate how the framework improves security resilience by focusing more on the human as a driver and user throughout the system, enabled by technological tools that start with the development of more diverse rules for data analytics through inputs from of federal, state, local, territorial, tribal, provincial, and private sector operators.